2020
DOI: 10.1029/2020gl089682
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Fluid Invasion Patterns in Porous Media

Abstract: Fluid invasion into porous media to displace a more viscous fluid exhibits various displacement patterns. For such unfavorable displacements, previous works overlooked the dynamic effect of viscous force on pattern transitions at low flow rates. Consequently, the crossover from compact displacement to capillary fingering under various wetting conditions remains unclear. Here, we establish a theoretical model to capture pattern transitions affected by wettability and flow rate. We rigorously quantify the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
6
35
0
Order By: Relevance
“…Given the focus of this work is the drainage displacement with θ = 120°, the 3D nature of pore‐scale flow behaviors including wetting film (Levaché & Bartolo, 2014) and corner flow (Concus & Finn, 1969; Zhao et al., 2016) can be neglected. Thus, the overlap is controlled by the in‐plane curvature (Hu et al., 2018b; Lan et al., 2020). The occurrence of pore‐filling events was employed to predict the transition from capillary fingering to compact displacement in porous media with a fixed pore‐scale disorder λ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the focus of this work is the drainage displacement with θ = 120°, the 3D nature of pore‐scale flow behaviors including wetting film (Levaché & Bartolo, 2014) and corner flow (Concus & Finn, 1969; Zhao et al., 2016) can be neglected. Thus, the overlap is controlled by the in‐plane curvature (Hu et al., 2018b; Lan et al., 2020). The occurrence of pore‐filling events was employed to predict the transition from capillary fingering to compact displacement in porous media with a fixed pore‐scale disorder λ .…”
Section: Resultsmentioning
confidence: 99%
“…As previously discussed in Figure 5, the underlying mechanism of this transition is that the overlap event dominates multiphase flow in the domain of compact displacement (Figure 5a). Note that even under such slow flow rate conditions (–7.4 ≤ log 10 Ca ≤ −6.9) in which the fluid displacement is capillary‐dominated, the transition from compact displacement to capillary fingering also depends on flow rate (Lan et al., 2020). It suggests that under such a range of capillary numbers, the viscous pressure cannot be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…This study was complemented by Lan et al. (2020), who used a dynamic pore-network model to explore the interplay between wettability and for which, like the model of Holtzman & Segre (2015), neglected corner flow and was therefore limited to . The phase diagrams produced in these studies correspond to a set of partial slices of the diagram we present in our manuscript.…”
Section: Introductionmentioning
confidence: 95%
“…2016; Lan et al. 2020). We observe the same trend for all degrees of disorder: both the finger width and the fractal dimension are consistently higher in imbibition than in drainage (figure 16 b , c ).…”
mentioning
confidence: 99%
“…Zhao et al (2016) found in microfluidic experiments involving vertical posts representing a porous medium, that as wettability is increased, there is more efficient displacement and higher saturation up until a critical angle is reached, after which, the system undergoes a wetting transition and the trend is reversed. Other microfluidic research combined with theoretical analysis and pore-scale simulations (Hu et al 2019;Lan et al 2020) have studied the phase diagram capturing the viscous to capillary fingering transition to study the impact of medium disorder and wettability on this transition. Research using an invasion-percolation model by Primkulov et al (2018) extended the Cielpak and Robbins description of quasistatic fluid invasion reproducing the wetting transition in strong imbibition.…”
Section: Introductionmentioning
confidence: 99%